(untitled) (Scientific journal of the Fergana State University, 2023)
This article empirically analyzes the geoeconomic concept of the famous French scientist, essayist, economist, professor, former adviser to the President of the French Republic F. Mitterand, former chairman of the EBRD. The main attention is paid to the analysis of the factors that ensure peace, development, innovative approaches to history and the universal order. The article also provides good recommendations on social studies.